Kadınların adalete erişimi mevzuat, engeller, uygulamalar ve sivil toplumun rolü - Ayata, Gökçiçek (İstanbul Bilgi Üniversitesi, 2009)
[Abstract Not Available]
Women's access to justice: legislation obstacles, practices and civil society's role